Identify the needs for continuous professional training of specialists working with juvenile delinquents in order to make the intervention more effective and increase the chances of social adaptation - Toma, Cristina Magdalena (Technium Social Sciences Journal, 2022)
Youth deviance is one of the fundamental problems of any society. Over time, the problem of young people's adaptation to the group they belong to, the stages of socialization, internalization and compliance with the rules imposed by the majority, as well as the inability of some individuals to adapt to the demands of social life in common, have been food for thought and a framework for scientific debate. Despite the efforts of state institutions, police, prosecutors, courts, schools, juvenile delinquency cannot be stopped. But it can be reduced if a series of appropriate social and criminal measures are implemented. Minors and young people have developing personalities and working with these categories must be guided by the principle of "not adapted to the prison - adapted to the social". Thus, the activities carried out with juvenile delinquents must aim to maintaining a permanent connection with the external social environment, developing certain social skills, increasing their educational level and facilitating their socio-occupational integration. The intervention on juvenile delinquency must start from the intervention on the individual and continue with the intervention on the specialists who work with this category, going up to formulating recommendations on the conditions in which the educational approaches in prison can be optimally carried out. In the light of the new European legislation on the social reintegration of the formerly imprisoned, a new perspective is emerging. Each prisoner is "invited to contribute to their own positive change" (Gheorghe, 2016, p. 210). However, the determined role in the development of effective interventions lies with the penitentiary system, through the social actors involved, especially the specialists who carry out educational activities. The research aims at identifying the training needs of staff working with juvenile delinquents and those at social risk.